Insights into fungal communities in composts revealed by 454-pyrosequencing: implications for human health and safety - De Gannes, Vidya; Eudoxie, Gaius; Hickey, William J. (Frontiers in Microbiology, 2013)
Fungal community composition in composts of lignocellulosic wastes was assessed via 454-pyrosequencing of ITS1 libraries derived from the three major composting phases. Ascomycota represented most (93%) of the 27,987 fungal sequences. A total of 102 genera, 120 species, and 222 operational taxonomic units (OTUs; >97% similarity) were identified. Thirty genera predominated (ca. 94% of the sequences), and at the species level, sequences matching Chaetomium funicola and Fusarium oxysporum were the most abundant (26 and 12%, respectively). In all composts, fungal diversity in the mature phase exceeded that of the mesophilic phase, but there was no consistent pattern in diversity changes occurring in the thermophilic phase. Fifteen species of human pathogens were identified, eight of which have not been previously identified in composts. This study demonstrated that deep sequencing can elucidate fungal community diversity in composts, and that this information can have important implications for compost use and human health.